Evaluasi Ketidaktepatan Pemilihan Obat Berdasarkan Kriteria STOPP Pada Pasien Geriatri - Santi Dwi Astuti; Nila Darmayanti Lubis; Fitri Kurniasari (Fakultas Farmasi Universitas Setia Budi, 2017)
ABSTRACTOlder patients have various comorbidities with a variety of prescribed treatments, therefore the Adverse Drug Events rate increases. This is due to physiological changes associated with age and body composition of the impact of aging processes that are universal in the form of decreased cell, tissue and organ functions that are progressive and gradual affecting the condition and response of drugs in the body of elderly patients. The STOPP criteria contains inappropriate medications given to elderly patients.The study was a retrospective analytics, consisting of two study groups: the right group of patients undergoing treatment and an inappropriate group of patients undergoing treatment. Research data taken is geriatric patient data.Treatment based on STOPP criteria from 70 geriatric patients consisted of 33 male patients (47%) and 37 female patients (53%). A total of 51 patients (73%) received appropriate treatment, while 19 patients (27%) received inappropriate treatment. Treatments include cardiovascular, antiplatelet and anticoagulant medications, central nervous system and psychotropic drugs, renal system, gastrointestinal system, respiratory system, muscle and skeletal system, endocrine system, analgesic drug. The group who received inappropriate treatment had an occurrence of Side Effects Drugs include heart palpitations, nausea, vomiting and constipation.